Pemahaman Peserta Didik Mengenai Dampak Penggunaan Gadget - Muslimah, Shinta; Putra, Fuaddhilah; Chandra, Yasrial (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This research was prompted by observations of students exhibiting various unfocused behaviors during class, such as playing games, taking photos, and using social media. Additionally, some students struggled with socializing and maintaining concentration while learning. The study aimed to describe students' understanding of: 1) the positive impacts of gadget use, and 2) the negative impacts of gadget use. Employing a quantitative descriptive analysis method, this research included a population of 42 students. Total sampling was used to select participants, and data was collected via questionnaires. The findings reveal that students' understanding of the positive impacts of gadget use was in the